2006
DOI: 10.1007/s11064-005-9012-8
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Characterization of SATB2, a Novel AT-rich DNA Binding Protein Expressed in Development- and Cell-Specific Manner in the Rat Brain

Abstract: AT-rich DNA elements play an important role in regulating cell-specific gene expression. One of the AT-rich DNA binding proteins, SATB1 is a novel type of transcription factor that regulates gene expression in the hematopoietic lineage through chromatin modification. Using DNA-affinity purification followed by mass spectrometry we identified and isolated a related protein, SATB2 from the developing rat cerebral cortex. SATB2 shows homology to SATB1 and the rat protein is practically identical to the mouse and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
103
0
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(114 citation statements)
references
References 57 publications
7
103
0
1
Order By: Relevance
“…However, we have found that SATB1 is identical to the 100-kDa AT-rich dsDNA-binding protein (tentatively named as dAT2). SATB1 (and also its related protein SATB2) are also expressed in development-and cell-specific fashion in the rat brain and are involved in regulating gene expression in differentiating neurons (33). 5 Many AT-binding proteins have a specific domain, called the AT-hook, thought to be critical to bind to AT-rich dsDNA sequences (51).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, we have found that SATB1 is identical to the 100-kDa AT-rich dsDNA-binding protein (tentatively named as dAT2). SATB1 (and also its related protein SATB2) are also expressed in development-and cell-specific fashion in the rat brain and are involved in regulating gene expression in differentiating neurons (33). 5 Many AT-binding proteins have a specific domain, called the AT-hook, thought to be critical to bind to AT-rich dsDNA sequences (51).…”
Section: Discussionmentioning
confidence: 99%
“…Following pentobarbital anesthesia, rat embryos were obtained from timed pregnancies; the brains were removed, and striatal and cortical primary embryonic neuronal cultures were prepared and maintained as published previously (29). C6 cells were obtained from the ATCC and cultured as described previously (33). For DNA molecular decoy assays, primary neuronal cultures were cotransfected with a DNA mixture containing the following: 0.5 g of the reporter plasmid 2700/ 703ENK-Luc, 2 g of competitor dsDNA corresponding to the rAT ENK region, or a control dsDNA (rAT ENK mut ) as described for EMSA above and 0.1 g of pCMV-Renilla luciferase.…”
Section: Methodsmentioning
confidence: 99%
“…Satb2 is expressed by a subset of neurons throughout the cortical layers, but its expression is most prominent in layers 2-4 [18,[48][49][50]. Targeting of the Satb2 locus with a lacZ gene revealed that Satb2 expressing neurons normally extend axons across the corpus callosum [49].…”
Section: Satb2 and The Determination Of Callosal Projection Neuron Idmentioning
confidence: 99%
“…2 The SATB2 protein is involved in chromatin remodeling and transcriptional regulation through its ability to bind AT-rich DNA sequences known as matrix attachment regions (MAR). 3,4 Depending on the locus, it can either repress or activate transcription of specific genes. 5 Chromosomal translocations disrupting SATB2 have been associated with cleft palate (CP) and learning difficulties (OMIM #119540).…”
Section: Introductionmentioning
confidence: 99%